Linking part design to process planning by design for additive manufacturing ontology - Witherell, Paul (2018)
Design for additive manufacturing (DFAM) provides design freedom for creating complex geometries and guides designers to consider manufacturing constraints during product design. However, DFAM is still developing to formalize and structure design guidelines for additive manufacturing. Therefore, this paper presents a DFAM knowledge base that contains a wide range of information including design features, manufacturing features, and parameters. The knowledge base is formalized by web ontology language (OWL) and is called as DFAM ontology in this study. The manufacturing feature concept is defined to link part design to AM process parameters. Since manufacturing features contain information on AM constraints, the DFAM ontology contributes to analyzing manufacturability of design features according to AM processes.